A hybrid global optimisation algorithm based on locally filled functions and cluster analysis. (22nd April 2008) - Huang, Hong-Xuan; Zhao, Yu
In this paper we will extend the definition of a filled function and propose a new definition of a locally filled function. The difference between the locally filled function and the classical filled function is illustrated by an example. The existence of a locally filled function is also studied in theory. Based on the locally filled function and cluster analysis technique we will present a hybrid global optimisation algorithm. The algorithm integrates the deterministic and stochastic searching techniques and has a very powerful globally searching ability. Numerical performance of the new hybrid algorithm is demonstrated by two examples about the Shubert I and Sine-Square I functions.